NRX-101 (D-Cycloserine + Lurasidone) Is Active against Drug-Resistant Urinary Pathogens In Vitro - Michael T. Sapko; Michael Manyak; Riccardo Panicucci; Jonathan C. Javitt (MDPI AG, 2024)
D-Cycloserine (DCS) is a broad-spectrum antibiotic that is currently FDA-approved to treat tuberculosis (TB) disease and urinary tract infection (UTI). Despite numerous reports showing good clinical efficacy, DCS fell out of favor as a UTI treatment because of its propensity to cause side effects. NRX-101, a fixed-dose combination of DCS and lurasidone, has been awarded Qualified Infectious Disease Product and Fast Track Designation by the FDA. In this study, we tested NRX-101 against the urinary tract pathogens Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumoniae, and Acinetobacter baumannii in cation-adjusted Mueller-Hinton broth (caMHB) and artificial urine media (AUM). Several strains were multidrug resistant. Test compounds were serially diluted in broth/media. Minimum inhibitory concentration (MIC) was defined as the lowest concentration of the test compound at which no bacterial growth was observed. DCS exhibited antibacterial efficacy against all strains tested while lurasidone did not appreciably affect the antibacterial action of DCS in vitro. In AUM, the MICs ranged from 128 to 512 mcg/mL for both DCS and NRX-101. In caMHB, MICs ranged from 8 to 1024 mcg/mL for NRX-101 and 32 to 512 mcg/mL for DCS alone. Our data confirm that DCS has antibacterial activity against reference and drug-resistant urinary pathogens. Furthermore, lurasidone does not interfere with DCS's antimicrobial action in vitro. These results support the clinical development of NRX-101 as a treatment for complicated urinary tract infections.